(untitled) (Global Journal of Human-Social Science, 2012)
In previous decades, decision making in water management problems and selection of better option among suggested options to solve a watershed problems was only done based on economical criteria -profit in relation to cost-and on changing social and environmental criteria in to the economical criterion. However, today using Multi criteria decision making, it is not necessary to use financial equivalent of social and environmental criteria to select the best option. In fact, various qualitative and quantitative criteria can be used to prioritize and select the best options for water resources management. The purpose of this study is ranking the water resources potential in Zarand-Saveh watershed by two methods; ELECTRE method and Linear Assignment. ELECTRE method is one of the Multi criteria decision making which can compound the quantitative and qualitative criteria, weight each criterion based on its importance and help decision makers to select the best option at the same time. Electrical method is one of the available methods in compensatory methods. In this method, all options are analyzed and evaluated by non-ranked comparisons. Whole stages of this method are based on coordinated and uncoordinated sets and thus it is called "coordination analysis".